2018
DOI: 10.1002/ldr.3061
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climate and land use changes on recent trends of soil erosion rates within the Russian Plain

Abstract: The Russian Plain (within the Russian Federation) occupies an area of approximately 3.5 × 106 km2. Water erosion is the main land degradation factor within the Russian Plain. Previous quantitative assessments of erosion rates for the entire area of the Russian Plain were undertaken in the 1980s. The application of erosion models and analysis of different factor dynamics allow for the evaluation of the mean annual total soil losses and erosion rates for the post‐Union of Soviet Socialist Republics period, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…González‐Arqueros, Navarrete‐Segueda, and Mendoza (2018) and Kijowska‐Strugała, Bucała‐Hrabia, and Demczuk (2018) applied modelling and statistical approaches in the Teotihuacan and Aztec Periods in Mexico, and the last 160 years in the Polish Carpathians, respectively, and found soil erosion to be more related to landuse than to climate changes. Golosov et al (2018) modelled run‐off and snow‐melt erosion, recognized abandonment of agricultural land to be responsible for decreased erosion rates in the last 30 years in the Russian plains, and suggested that snow‐melt erosion is influenced by changing winter air temperature patterns.…”
Section: Timeliness and Relevance Of The Issuementioning
confidence: 99%
“…González‐Arqueros, Navarrete‐Segueda, and Mendoza (2018) and Kijowska‐Strugała, Bucała‐Hrabia, and Demczuk (2018) applied modelling and statistical approaches in the Teotihuacan and Aztec Periods in Mexico, and the last 160 years in the Polish Carpathians, respectively, and found soil erosion to be more related to landuse than to climate changes. Golosov et al (2018) modelled run‐off and snow‐melt erosion, recognized abandonment of agricultural land to be responsible for decreased erosion rates in the last 30 years in the Russian plains, and suggested that snow‐melt erosion is influenced by changing winter air temperature patterns.…”
Section: Timeliness and Relevance Of The Issuementioning
confidence: 99%
“…The average soil erosion rate on the arable land in the territory studied amounts to 4.04 t ha −1 yr −1 , considering the soil-protective coefficients of crops. In the annual soil loss by erosion, storm runoff erosion prevails at 3.78 t ha −1 yr −1 and the erosion by snowmelt is considerably lower at only 0.26 t ha −1 yr −1 [30,31].…”
Section: Territory Under Studymentioning
confidence: 98%
“…В основном это связано с тем, что в России низкий уровень водной эрозии почв, а также трансформации естественных ландшафтов под пашню. Это совпадает со многими современными оценками российских ученых, которые фиксируют снижение текущего уровня эрозии на возделываемой пашне по сравнению с 1980-ми годами [13][14][15]. Однако выбор дальнейших путей развития нуждается в определении конкретных регионально (или даже локально) специфических стоимостных оценок эффективности использования сельскохозяйственных земель.…”
Section: экономическая оценка восстановления и увеличения эффективнос...unclassified